Biomarkers of visual perception dysfunction in autism: Progress and directions in EEG research - Feroz, Farah Shahnaz; Shahbodin, Faaizah; Che Ku Mohd, Che Ku Nuraini; Jano, Zanariah; Mohamad, Siti Nurul Mahfuzah; Riza, Lala Septem; Munir; Rasim (MEDSPORTPRESS Publishing House, 2022)
As the world moves towards the Fourth Industrial Revolution, there is a need for formulations of neurophysiological bio-markers that ensure the accuracy of the diagnosis of visual perception dysfunction in individuals with Autism Spectrum Disorder (ASD). Biomarkers of visual perception dysfunction in ASD using EEG complements behavioral methods of diag - nosis and allows for a more direct assessment of the dys function, identifying rapid, implicit neural processes that are not revealed through behavioral measures alone. This paper aims to review the neural biomarkers of the five domains of visual perception dysfunction (visual discrimination (VD), visual spatial relations (VSR), visual form constancy (VFC), visual memory (VM) and visual closure (VC)) in individuals with ASD. This paper shall help researchers gain new insight into the current trends and progress in EEG methods in ASD and discover gaps in the subject literature. A systematic literature search on PubMed was conducted to report findings of EEG studies that: 1) assessed the severity levels in patients with ASD and 2) investigated the neural bio-markers of visual perception dysfunction in ASD. Spectral analysis, functional connectivity analysis and event-related potential (ERP) are useful in modern medicine to identify the biomarkers that distinguish the levels of the severity of visual perception dysfunction in ASD